Electroencephalographic responses to low and high voltage of electroejaculator used for semen collection in bulls - Nadhirah Yahaya,
Electroejaculation (EE) is one of the routine procedure used to collect semen for breeding programme and bulls soundness evaluation at the farm. No concrete conclusion regarding pain produced by EE has been reported. Electroencephalography (EEG) is an objective tool to evaluate pain in recently reported studies. No EEG study on evaluating pain associated with EE has been reported. Therefore, this study was designed to compare the EEG responses and the behaviour changes to low (≤6) and high (>6) voltage of the electro-ejaculator in bulls. A total of eight bulls of 2 years age and average of 200kg body weight were used in this study. Bulls were attached with two EEG adhesive electrodes on their head and the EEG and behaviour were recorded for 5 minutes, before EE (baseline), during EE and 20 minutes after EE. Analysis of EEG was performed offline after the end of experiments. The results revealed that EEG parameters increased significantly during EE compared to baseline and returned towards baseline 20 minutes after EE. Median frequency, an indicator of pain increased significantly compared to baseline in both high and low voltage groups. Furthermore, significant increases (p=0.0001) was observed in low voltage group (47.14±6.67) animals compared to the animals in the high voltage group (32.66±4.53). Total power also increased significantly (p=0.0001). The bulls in both groups showed behavioural changes such as arched back, salivation and struggling during the EE for semen collection. Overall, the increment of EEG responses and behavioural changes during EE suggests that the semen collection using EE is painful. Future studies to consolidate the findings of this study with the stress hormone analysis along with EEG are recommended.